Seasonal variations in mineral status of reindeer calves from Elgaa reindeer herding district, Norway - Staaland, Hans; Sæbø, Stein (Rangifer, 1987)
Botanical analyses of rumen content from reindeer calves slaughtered during the period August to April showed dominance of grasses (36%), lichens (30%) and woody plants (21 %). Na content in rumen, bone, liver and muscle samples increased from August to April, whereas K and Mg decreased. It is suggested that the high level of K in summer forage'increases Na excretion and drains the body reserves of this mineral. The body reserves of Na are apparently rebuilt through fall and winter.Sesongvariasjoner i mineralstatus hos reinkalver fra Elgå reinbeitedistrikt.Abstract in Norwegian / Sammendrag: Botaniske analyser av vominnhold fra reinkalver som ble avlivet i perioden august til april viste dominans av gress (36%), lav (30%) og treaktige planter (21%). Innholdet av Na i vom, bein, lever og muskelprøver økte fra august til april, mens K og Mg avtok. Det blir antydet at det høye nivået av K i sommerbeite øker ekskresjon av Na og minsker kroppsbeholdningen av dette mineralet. Kroppsreservene av Na synes å bli bygget opp igjen i løpet av høst og vinter.